Effectiveness of knowledge translation and knowledge appropriation of clinical practice guidelines for patients and communities, a systematic review - Nathaly Garzón-Orjuela; Javier Eslava-Schmalbach; Nathalie Ospina (Biomédica, 2018)
Introduction: Knowledge translation and knowledge appropriation social interventions apply knowledge to improve health services and outcomes. These interventions can be implemented routinely to improve patient adherence to clinical practice guidelines. Objective: To assess the effectiveness of knowledge translation interventions to improve patient and community adherence to clinical practice guidelines. Materials and methods: We performed a systematic review of these interventions compared with classical interventions for patients and/or communities. We searched the following electronic databases up to April 2017: Medline (Ovid), Embase, Scopus, Central (Ovid), Web of Science, LILACS, Academic Search, and Scielo. Two independent raters qualified the relevance, risk of bias, and quality of included studies. Results: Eight studies were included. Patient adherence to recommendations was observed in two studies. There was high heterogeneity due to the variability of the population, types of guidelines, and types of measurement tools. The risk of bias was high: a 60% risk of performance bias, 50% risk of attrition bias, 25% risk of selection and reporting bias, and 15% risk of detection bias. The quality of evidence was moderate for the outcomes of adherence and mortality. The interventions that used a combination of strategies, such as with the group of health professionals, could improve some clinical outcomes in the patients (Average deviation: -3.00; 95% IC: -6.08-0.08). Conclusions: Knowledge translation interventions might have a slight positive effect on patient adherence and some short-term clinical outcomes, particularly within mixed interventions (patients and health professionals). However, future studies with less heterogeneity are necessary to confirm these results.